Heart of Learning: Pedagogical Practices Amongst Islamic Education Novice Teachers in the 21st Century - Tengku Kasim, Tengku Sarina Aini; Abdurajak, Fatimah Sahida (Jurnal Usuluddin, 2018)
A number of issues and challenges have been faced by novice teachers such as the difficulties in translating their knowledge into action, managing the classroom, finding suitable teaching approaches and more. Thus, this study seeks to address and examining the understanding and pedagogical practices of novice teachers as they grapple with essential aspects of teaching. Moreover, it provides an insight into the actual application of their teaching and learning approaches which they adopt throughout a limited experience during their initial years of teaching. This study was conducted on ten Islamic education novice teachers in secondary schools from four different states in Malaysia. The data were collected by using semi-structured individual interviews. The results that emerge from these findings are teachers’ application of using student-centred learning and their acceptance in imposing 21st Century Education.